Methodological problems in a study of fetal visual perception - Scheel, Anne M.; Ritchie, Stuart J.; Brown, Nicholas J.L.; Jacques, Steven L. (Current biology, 2018)
Reid et al.[1] analysed data from 39 third-trimester fetuses, concluding that they showed a preferential head-orienting reaction towards lights projected through the uterine wall in a face-like arrangement, as opposed to an inverted triangle of dots. These results imply not only that assessment of visual-perceptive responses is possible in prenatal subjects, but also that a measurable preference for faces exists before birth. However, we have identified three substantial problems with Reid et al.’s [1] method and analyses, which we outline here. A recent study on visual perception in human fetuses suggested that a preference for face-like shapes may be present before birth. Scheel et al. comment on this study, describing three methodological and analytical problems that call its conclusions into question.